Fostering Inclusive Law Enforcement: Integrating Multicultural Education and Islamic Character Development at Indonesia’s Police Academy - Basir, Abdul; Mulyoto, Mulyoto; Hasyim, A. Dardiri (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study aims to explore the integration of multicultural education and Islamic character development among police students at Sekolah Polisi Negara (SPN), Indonesia. Multicultural education plays a pivotal role in fostering inclusivity and understanding in diverse societies, particularly in a multicultural country like Indonesia. Given SPN's significance in shaping future law enforcement officers, understanding the role of multicultural education and Islamic character development is crucial. This qualitative study engaged with SPN students, instructors, and administrators to investigate the strategies and approaches employed in integrating multicultural education and Islamic values into the curriculum. Findings reveal a comprehensive approach that emphasizes cultural understanding, respect, and empathy among students while incorporating teachings from Islamic jurisprudence to align professional conduct with ethical principles. Through narrative analysis, this study sheds light on the multifaceted dimensions of multicultural education and Islamic character development at SPN, offering insights into the preparation of culturally competent and ethically grounded law enforcement officers in a diverse society.